(untitled) (Journal of Armed Forces Medical College, Bangladesh, 2021)
Introduction: Herpes zoster (HZ) is characterized by an extremely painful vesicular rash, which may be complicated by secondary infection and post-herpetic neuralgia. To date, multiple risk factors associated with HZ have been established, including endocrine diseases, immunosuppressive conditions, cancers, and other chronic medical conditions. Objectives: To assess the profile of herpes zoster associated with co-morbid condition. Methods and Materials: This cross sectional study was conducted among purposively selected 130 HZ patients in the department of Dermatology and Venereology, Combined Military Hospital (CMH) Dhaka from January 2017 to December 2018. Data were collected through face to face interview using pretested semi-structured questionnaire. Results: Out of 130 patients, majority of the patients were male (69.2%) and mean age was 53.5±9.8 years and majority gave the history of chicken pox 60% and common site of involvement were chest (right and left) 33.1% and 48.5%, upper back (right and left) 30.8% and 43.1% and upper right arm 33.1%. About 66.9% patients gave the history of having co-morbid condition like Diabetes 30.8%, Stroke 9.2%, Hypertension 2.3%, Myocardial infarction 3.8%, Peptic ulcer disease 10.0%, Malignancy 2.3%, Tuberculosis 2.3% and Irritable bowel syndrome 2.3%. Conclusion: Based on our study finding, we can conclude that herpes zoster is a disease that is associated with other co-morbid conditions. If herpes zoster is an early manifestation of undiagnosed co-morbid condition, patients should undergo testing for undiagnosed disease when they present with herpes zoster. JAFMC Bangladesh. Vol 16, No 2 (December) 2020: 40-43